Analysis of injury characteristics in youth elite football athletes in Indonesia - Benidektus Adi Prianto; Tommy Apriantono; Hamidie Ronald Daniel Ray; Nur Luthfiatus Solikah (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Background: Football is the most popular sport globally, with approximately 200,000 professional players and 240 million amateur players. It is a high-intensity intermittent sport that can lead to fatigue, increasing the risk of injury. Unfortunately, injuries in young athletes are still not widely studied, making not much data available. This study tries to fill the gap by investigating the characteristics of injuries in young football athletes in Indonesia. In addition, it attempts to determine the relationship between BMI, exposure time to training and matches on injuries. Methods: This study used a retrospective cohort design with a survey method on EPA (Elite Pro Academy) U14, U16, and U18 youth football athletes from 18 teams in each age group. The data were collected from 838 young footballers as the sample. Results: This study found no association between BMI and injury (p > 0.05), while exposure time did have an association with injury (p < 0.05). Based on the injury location, sports injuries were mostly found in the ankle 273 (39%). The highest injury type was contusion 36%, followed by strain 25% and sprain 18%. Regarding severity, most cases were classified as minor injuries (4-7 days), with 299 (43%). The defender position had the most injuries, 188 (35%). Osgood Schlatter was most prevalent in athletes aged 13, with 29 cases. Meanwhile, the total injury incidence is 3.9/1000 hours. Conclusions: This study found that training exposure time was associated with the number of injuries. It also recorded that most injuries occur in the lower limbs, especially ankle ligament injuries. The defender received high attention as it is considered the most vulnerable position. Finally, the peak incidence of Osgood Schlatter occurred at the age of 13.